Analysis Of Health Care Quality Evaluation Of Patient Satisfaction In Health District Genyemdistrik Nimboran Jayapura - Tebay, Vince; Fatem, Agustinus; Wati, Risna (Advances in Social Sciences Research Journal, 2017)
Health development aims to provide the widest opportunity for the community, and the government has also provided some means or health facilities that can be used by the community in order to Obtain optimal health status and it is manifested Among other things by building health centers throughout Indonesia , This study aims to identify and evaluate the quality of health services performed by health workers to the satisfaction of Patients undergoing treatment at the health center Genyem. This study to analyze the description of the variable quality of services that include: physical evidence, Reliability, Responsiveness, Assurance and Empathy at the health center in simultaan Genyem and partially significant to satisfaction of Patients in health centers Genyem. The Data in this study were Directly Obtained by distributing questionnaires that have been provided. Multiple linear regression analysis to control classical assumption (normality, autorelation and multikolioneritas) Became the main models chosen in research, having escaped the validity and reliability of the instrument can be concluded: 1. Quality of service include: physical evidence, reliability, responsiveness, assurance and empathy in health center Genyem got good perception of the patient; 2. Variable physical evidence, reliability, responsiveness, assurance and empathy simultaneously (together - the same) Significantly Affects patient satisfaction; 3. Based on the SWOT analysis, found the barriers - barriers faced by PHC Chief and Health Officer in terms of improving patient satisfaction and Formulated a strategy - a strategy that can be applied to improve patient satisfaction.